2021
DOI: 10.1111/cas.14799
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical and clinical advances in dual‐target chimeric antigen receptor therapy for hematological malignancies

Abstract: Immunotherapy can mobilize the natural antitumor ability to achieve targeted elimination of tumor cells, with minimal toxicity to normal cells. Adoptive cell therapy has evolved over several generations, from the earliest lymphokine-activated killer cells (first generation) and cytokine-induced killer cells (second generation), to tumorinfiltrating lymphocytes (third generation), antigen-specific cytotoxic T lymphocytes (fourth generation), and chimeric antigen receptor (CAR; fifth generation) T cells. In rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 75 publications
0
16
0
Order By: Relevance
“…The improved PFS associated with tandem CAR T-cells whereas reduced PFS associated with co-infusion of CD19 and CD20 CAR T-cells versus Yescarta corroborates pre-clinical studies that demonstrated the higher efficacy and safety of tandem CAR T-cells than that of co-infusions (10). The reduced survival benefit and increased CRS associated with the co-infusion of different CAR T-cell targets may be associated with (1) additive toxicity from stronger cytokine storm through the amplified number of targetable antigens; (2) competitive targeting limit the expansion of other CAR T-cells; (3) compromised engraftment due to the interference of multiple antigens (12,50,51). Literature review on the multi-antigen targeting strategies show that there is more data for CD19 and CD22 covering various administration approaches (sequential and co-infusion) and different constructs (tandem and bicistronic).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The improved PFS associated with tandem CAR T-cells whereas reduced PFS associated with co-infusion of CD19 and CD20 CAR T-cells versus Yescarta corroborates pre-clinical studies that demonstrated the higher efficacy and safety of tandem CAR T-cells than that of co-infusions (10). The reduced survival benefit and increased CRS associated with the co-infusion of different CAR T-cell targets may be associated with (1) additive toxicity from stronger cytokine storm through the amplified number of targetable antigens; (2) competitive targeting limit the expansion of other CAR T-cells; (3) compromised engraftment due to the interference of multiple antigens (12,50,51). Literature review on the multi-antigen targeting strategies show that there is more data for CD19 and CD22 covering various administration approaches (sequential and co-infusion) and different constructs (tandem and bicistronic).…”
Section: Discussionmentioning
confidence: 99%
“…(2) competitive targeting limit the expansion of other CAR T-cells; (3) compromised engraftment due to the interference of multiple antigens (12,50,51). Literature review on the multi-antigen targeting strategies show that there is more data for CD19 and CD22 covering various administration approaches (sequential and co-infusion) and different constructs (tandem and bicistronic).…”
Section: Dual Targeting Strategies Versus Yescartamentioning
confidence: 99%
“…This finding corroborates preclinical studies that demonstrated the higher efficacy and safety of tandem CAR T-cells than that of co-infusions ( 10 ). The reduced survival benefit and increased CRS associated with the co-infusion of different CAR T-cell targets may be associated with: ( 1 ) additive toxicity from stronger cytokine storm through the amplified number of targetable antigens; ( 2 ) competitive targeting limiting the expansion of other CAR T-cells; ( 3 ) compromised engraftment due to the interference of multiple antigens ( 12 , 50 , 51 ). A literature review on the multi-antigen targeting strategies showed more data for CD19 and CD22 covering various administration approaches (sequential and co-infusion) and different constructs (tandem and bicistronic).…”
Section: Discussionmentioning
confidence: 99%
“…Although CAR-T cell therapy has made impressive achievements in R/R B cell malignancies, a majority of patients still relapse (143). One of the primary mechanisms of relapse after CAR-T cell therapy is antigen loss (169,170). The antigen mutations under therapeutic pressure of CAR-T cell therapy are the most common mechanisms of antigen loss, including splice variants, lineage switching, and biallelic mutations (171)(172)(173).…”
Section: Overcoming Antigen Escapementioning
confidence: 99%